Lymph Node Ratio-Based Staging System for Gallbladder Cancer With Fewer Than Six Lymph Nodes Examined - Li, Jinjun; Sun, Yao; Zhao, Bingqing; Tang, Chuangang; Fan, Dongxu; Jiang, Wenli; Rixiati, Youlutuziayi (Frontiers in Oncology, 2020)
Purpose The 8th edition of the American Joint Committee on Cancer (AJCC) tumor-lymph node-metastasis (TNM) staging system for gallbladder cancer (GBC) recommended that at least six lymph nodes (LNs) should be examined. But most patients with GBC had fewer than six LNs resected. This study aimed to establish an alternative index for assessing the LN status during the staging system for GBC patients with fewer than six LNs retrieved. Patients and Methods Patient data was extracted from the Surveillance, Epidemiology, and End Results (SEER) database (cases between 2004 and 2013). X-tile software was used to determine the optimal cutoff value for lymph node ratio (LNR) and a concordance index (C-index) was used to evaluate the discriminatory powers of the two staging systems. Results The majority of GBC patients in our cohort (1353, 78.5%) had fewer than six LNs examined. Among patients with inadequate LN examination, the higher number of LNs examined correlated with a lower proportion of patients. Using the TNM staging system, the C-index for patients with fewer than six LNs and patients with six or more LNs screened were 0.636 and 0.704, respectively. Using the staging system based on LNR (TNrM), the C-index for patients with fewer than six LNs retrieved and patients with six or more LNs retrieved were 0.649 and 0.694, respectively. Similar results were observed in patients with gallbladder adenocarcinoma (GBA). Conclusion TNrM might be superior to the 8th AJCC TNM staging system for stratifying GBC patients with fewer than six LNs examined, and it can complement TNM for more accurate risk stratification. Future prospective studies are needed to validate our findings.